Wykorzystanie funkcji dyskryminacyjnych do prognozowania upadku przedsiębiorstw - Twardochleb, Barbara (The Usage of Discriminant Functions to Predict Bankruptcy of Companies, 2006)
This article presents the usage of multiplies discriminant analysis (MDA) for the construction of linear discriminant function W(X), which is effective in classifying bankrupt and nonbancrupt companies on Warsaw Stock Exchange for one year prior to failure. The value of discriminant function and the change in time can be used to predict financial distress of companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 317-327